Effects of prenatal mindfulness-based childbirth education on child-bearers’ trajectories of distress: a randomized control trial - Marissa D. Sbrilli; Larissa G. Duncan; Heidemarie K. Laurent (BMC Pregnancy and Childbirth, 2020)
Abstract Background The perinatal period is a time of immense change, which can be a period of stress and vulnerability for mental health difficulties. Mindfulness-based interventions have shown promise for reducing distress, but further research is needed to identify long-term effects and moderators of mindfulness training in the perinatal period. Methods The current study used data from a pilot randomized control trial (RCT) comparing a condensed mindfulness-based childbirth preparation program—the Mind in Labor (MIL)—to treatment as usual (TAU) to examine whether prenatal mindfulness training results in lower distress across the perinatal period, and whether the degree of benefit depends on child-bearers’ initial levels of risk (i.e., depression and anxiety symptoms) and protective (i.e., mindfulness) characteristics. Child-bearers (N = 30) in their third trimester were randomized to MIL or TAU and completed assessments of distress—perceived stress, anxiety, and depressive symptoms—at pre-intervention, post-intervention, six-weeks post-birth, and one-year postpartum. Results Multilevel modeling of distress trajectories revealed greater decreases from pre-intervention to 12-months postpartum for those in MIL compared to TAU, especially among child-bearers who were higher in anxiety and/or lower in dispositional mindfulness at baseline. Conclusions The current study offers preliminary evidence for durable perinatal mental health benefits following a brief mindfulness-based program and suggests further investigation of these effects in larger samples is warranted. Trial registration The ClinicalTrials.gov identifier for the study is: NCT02327559 . The study was retrospectively registered on June 23, 2014.